Gender Stereotypes and Figurative Language Comprehension - Roberta Cocco; Francesca Ervas (Humana.Mente: Journal of Philosophical Studies, 2012)
The paper aims to show how and to what extent social and cultural cues influence figurative language understanding. In the first part of the paper, we argue that social-contextual knowledge is organized in “schemas” or stereotypes, which act as strong bias in speaker’s meaning comprehension. Research in Experimental Pragmatics has shown that age, gender, race and occupation stereotypes are important contextual sources of information to interpret others’ speech and provide an explanation of their behavior. In the second part of the paper, we focus on gender stereotypes and their influence on the comprehension of figurative language, to show how the social functions of figurative language are modulated by gender stereotypes. We provide then an explanation of gender stereotypical bias on figurative language in terms of possible outcomes in the social context.